Technology Integrated with Metacognitive Regulation Approach as Natural Formula for Connecting Mastery and Effective Learning in Mathematics - Bakar, Mohamad Ariffin Abu; Ismail, Norulhuda (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to look at the effectiveness of mathematical learning through a metacognitive regulation approach with the technology integrated through modules, kits and interactive activities. Metacognitive regulation skills are students’ ability to manage their learning by planning, monitoring and evaluating. The combination of technology has created the motivation and impetus for meaningful learning. The objective of this study was to look at the impact of using the Meta-Seller Tutoring module and mathematics learning kit on the metacognitive regulation skills and mastery of student mathematics concepts. Based on quantitative approach using experimental design, the present study involved 159 students from three secondary schools. The results show that the use of modules combined with technology and metacognitive regulation strategies has the greatest impact on the metacognitive regulation skills and students’ mastery of mathematics concepts in shaping effective learning. The implications indicate that, teachers need to increase their knowledge of the latest pedagogy and improve their teaching design skills based on current technologies and trends. The parties need to look at approaches in the current curriculum to be more technology-friendly as well as apply learning strategies based on metacognitive skills that are seen as the best platform for improving students’ thinking skills.